Respuesta :
Answer:
[tex] \displaystyle a = \frac{1+vh}{v}[/tex]
Step-by-step explanation:
we want to figure out a value of a for the following condition
[tex] \displaystyle va - vh = 1[/tex]
to do so factor out v;
[tex] \displaystyle v (a - h )= 1[/tex]
divide both sides by v which yields:
[tex] \displaystyle \frac{(a-h) \cancel{(v)}}{ \cancel{v}}= \frac{1}{v} [/tex]
therefore,
[tex] \displaystyle a-h = { \frac{1}{v}}[/tex]
now,add h to both sides:
[tex] \displaystyle a = \frac{1}{v}+h[/tex]
further simplification if necessary:
[tex] \displaystyle a =\boxed{ \frac{1+vh}{v}}[/tex]
Given:-
- [tex]\sf{va-vh=1 }[/tex]
To find:-
- [tex]\sf{ value~ of ~a }[/tex]
Solution:-
- [tex]\sf{ va-vh=1 }[/tex]
factor out of v
- [tex]\sf{v(a-h)=1 }[/tex]
Dividing both sides by (v)
- [tex]\sf{\dfrac{v(a-h)}{(v)}=\dfrac{1}{(v)} }[/tex]
cancel out (v)
- [tex]\sf{\dfrac{\cancel{v}(a-h)}{\cancel{(v)}}=\dfrac{1}{(v)} }[/tex]
- [tex]\sf{ a-h=\dfrac{1}{v} }[/tex]
add h in both sides
- [tex]\sf{a-h+h=\dfrac{1}{v}+h }[/tex]
cancelout h
- [tex]\sf{a-\cancel{h}+\cancel{h}=\dfrac{1}{v}+h }[/tex]
- [tex]\sf{a=\dfrac{1}{v}+h }[/tex]
- [tex]\boxed{\sf{a=\dfrac{1+vh}{v} } }[/tex]
[tex]\sf{ }[/tex] [tex]\sf{ }[/tex]
Therefore:-
the value of a if va- vh is equals to 1 is [tex]\bold{\dfrac{1+vh}{v} }[/tex]